OVERVIEW CHARACTERISTICS AND P2Y12 REACTIVITY UNIT (PRU) VALUES OF ACUTE CORONARY SYNDROME AGE PRODUCTIVE PATIENTS WITH CLOPIDOGREL THERAPY - ., Rahmatini; Aliska, Gestina; Syafri, Masrul (UNUSA Press, 2017)
ABSTRACTBackground: Ischemic heart disease is the leading cause of death and disability in the world with a fairlyhigh portion coming from countries Low- and Middle-Income (LMICs). In Pakistan, 54% patients acutecoronary syndrome (ACS) was resistant to clopidogrel, and no data on clopidogrel resistance on ethnicMinang. This study aims to look at the characteristics and P2Y12 Reactivity Unit (PRU) from ACS patientsin Dr. M. Djamil Hospital, Padang. Methods: This research is a cross sectional study. The effectiveness ofclopidogrel on platelet reactivity identified through examination of PRU value using VerifyNow® with a cutoff point is 208. From the PRU values, it can be classified whether patients resistant or responsive. The studywas conducted in September 2016. Result: From 14 patients with ACS who received clopidogrel, 11 patients(78.57%) are male with 3 female patients (21.43). The mean of age was 53.78 years old. Patients mostlycame from West Sumatra provinces (92,85%) and 7,15% from others. From all of patients head risk factorsof coronary arterial disease. Hipertension was the greatest risk factor. Conclusion: It can be concluded thatmost of the patients were male. From PRU data, 7 patients (50%) were resistant and 7 patients (50%) wereresponse to clopidogrel. Further research is needed with larger numbers of patients and investigatepharmacogenetic profile of CYP2C19 as caused of resistance.